Peningkatan Kompetensi Guru SMP Negeri 37 Semarang melalui Pelatihan Penelitian Tindakan Kelas (PTK) - Rasiman Rasiman; Sutrisno Sutrisno; Kartinah Kartinah; Dina Prasetyowati (Pelita: Jurnal Pengabdian kepada Masyarakat, 2021)
Regulation of the Minister of Administrative Reform and Bureaucratic Reform No. 16 2009 on Functional and Credit Number of teacher, particularly clauses 17 explains that the nomination terms of teachers promotion must contain sub-elements of scientific publications on credit number. This Regulation shall come into effect on January 1th, 2013, it is different from previous years are only valid for teachers promotion IV/a upwards. Therefore, the need to write scientific papers is a very important requirement for teachers. It is also strongly felt by the teachers at Junior High School State of 37 Semarang as it has been presented by the Principal. To cultivate scientific writings in the teachers Junior High School State of 37 Semarang required training. IbM team of Universitas PGRI Semarang training classroom action research e.a. proposal writing, instruments, reports, scientific articles, up to its publication in a journal or proceedings. Outcomes of this devotion in the form of a Classroom Action Research proposal, Classroom Action Research instrument, Classroom Action Research reports, as well as scientific articles be published in a journal or proceedings.